An optimization-based method for prediction of lumbar spine segmental kinematics from the measurements of thorax and pelvic kinematics - Shojaei, I.; Arjmand, N.; Bazrgari, B. (International journal for numerical methods in biomedical engineering, 2015)
Summary Given measurement difficulties, earlier modeling studies have often used some constant ratios to predict lumbar segmental kinematics from measurements of total lumbar kinematics. Recent imaging studies suggested distribution of lumbar kinematics across its vertebrae changes with trunk rotation, lumbar posture, and presence of load. An optimization‐based method is presented and validated in this study to predict segmental kinematics from measured total lumbar kinematics. Specifically, a kinematics‐driven biomechanical model of the spine is used in a heuristic optimization procedure to obtain a set of segmental kinematics that, when prescribed to the model, were associated with the minimum value for the sum of squared predicted muscle stresses across all the lower back muscles. Furthermore, spinal loads estimated using the predicted kinematics by the present method were compared with those estimated using constant ratios. Predicted segmental kinematics were in good agreement with those obtained by imaging with an average error of ~10%. Compared with those obtained using constant ratios, predicted spinal loads using segmental kinematics obtained here were in general smaller. In conclusion, the proposed method offers an alternative tool for improving model‐based estimates of spinal loads where image‐based measurement of lumbar kinematics is not feasible. Copyright © 2015 John Wiley & Sons, Ltd. Distribution of lumbar kinematics across its vertebrae changes with task, load, and posture, therefore raising a concern related to such distribution using constant ratios. A biomechanical model of spine is used in an optimization procedure to predict a distribution of lumbar segmental kinematics, which is associated with the minimum level of stress among all trunk muscles. Predicted kinematics were in good agreement with those obtained by imaging, and spinal loads were smaller than those obtained by constant ratios.